Cryptosporidium: parasite and disease - Cacciò, Simone M.; Widmer, Giovanni (Springer Vienna : Imprint: Springer, 2014)
This new volume on Cryptosporidium and Cryptosporidiosis discusses all relevant aspects of the biology, molecular biology, host-parasite interaction, epidemiology as well as diagnosis and treatment of these widespread parasites. It represents a useful guide for physicians, microbiologists, veterinarians and water professionals seeking advanced knowledge and guidance about these important parasitic pathogens. A section on practical lab procedures discusses step-by-step guidelines for sample preparation and lab procedures. The new book may further serve as a reference work for graduate students in medical and veterinary microbiology.   .